The Effectiveness of the Implementation of Government Regulation Number 19 Year 2015 Regarding Non-Tax State Revenue at the Office of Religious Affairs - Ismail Ismail; Zainal Abidin; Muhtadin Dg. Mustafa (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2019)
The focus of this research is the effectiveness of the implementation of Government Regulation number 19 of 2015 about that applicable on the Ministry of religion and enforced in every area of the Religious Affairs Office on each sub includes Religious Affairs Office (KUA) Sub East of Palu. This regulation is about the cost of the wedding at the Religious Affairs Office of Rp 0.00 and when carrying out a wedding outside KUA or after hours are imposed on a tariff of 600.000.00. Rupiah This research used a qualitative descriptive method of data collection such as observation, interviews, and documentation. Data analysis used an analysis of the data reduction techniques, presentation, and data verification. The results show that the bride that is certainly true when implementing the marriage at the Office of religious affairs is not charged to tariffs and when carrying out weddings outside the Religious Affairs Office or outside working hours charged Rp. 600,000.00 paid in Bank BTN, MANDIRI, BNI, and BRI. However, generally the implementation of the Government Regulation number 19 no 2015 about tarrif non tax government revenue that applicable the Office of religious affairs of the subdistrict of East Palu has not been effective because there are still some elements that have not been fulfilled i.e.for example facilities and infrastructure that inadequate in providing the best service to the community if were continuing the wedding in the office of religion subdistrict of East Palu.